A Review of Literature on the Nature and Characteristics of University Staff Records - ILIYASU, SHUKURA SHARU; FARUK, BINTA (MiddleBelt Journal of Library and Information Science, 2020)
Universities undertake a number of human resource management functions, such as human resource planning, monitoring and policy development; establishment control; recruitment; appointment; performance appraisal; education; training and staff development; pay and allowances, promotions, transfers and secondments, disciplinary and grievance proceedings; attendance, leave and sickness; separation from employment through various reasons; pay and allowances. All these activities generate large quantity of records that need to be managed in recordkeeping system for easy access and use by authorized users. Staff records provide crucial information in all aspects of human resource administration. With all the benefits derived from staff records, an extensive literature search by the researcher revealed that academically, the area of staff records management is overlooked despite the fact that these record cause greatest challenges in their handling due to their bulk, longevity and sensitivity. This motivated the researcher to undertake this study. The objectives of the study is to find out the types of university staff record, nature and characteristic of the records, and the impact of changing technology on the nature and characteristics of the records. This study x-rays the concept, types and unique characteristics of staff records, taking into consideration the impact of changing technology on the nature and structure of staff records. Recommendations for the enhancement of staff records management are hereby provided. The universities should establish a formal policy specifically for accessing staff records, stating clearly, who will have the access to the records, purpose of accessing the records and the time to access the records. Accessibility to the staff records must be limited only to those in charge. The universities should provide modern electronic facilities for retaining staff records.